THE EQUATION ON THE JUSTICE FOR FISHERMAN: THE URGENCY TO PROTECT FISHERMEN AND MARINE RESOURCES IN INDONESIA - Dian Simanjuntak Narwastuty (Faculty of Law, Maranatha Christian University, 2020)
Indonesia’s territory has a lot of wealth in assets of marine resources and human resources. This wealth has become challenge for the Government of Indonesia to manage it. Nowadays, Indonesian marine is expected to be more developed, but in contrary, a lot of interest that should be regulating in the sea. The main questions that arouse are: how should government give an equation for Indonesian fisherman and how should the government put marine resources’ protection to supply the equation for natural resources. These questions will solve by a normative juridical study on the protection of natural resources and the resources of Indonesian fisherman. The study uses a descriptive analytical method for a number of regulations that apply in marine trade law and employment law. This research is also complemented by a literature approach in the form of Indonesian legal literature and marine journals to address the issues raised in this paper. The findings in practice prove that the government should give more attention for the fisherman’s welfare and protection related to fish catching. The objective protection for Indonesian marine resources is from regulated all the regulation to develop Indonesia economic from Maritime sector. It is all needed to make a new system in legal protection for Fisherman and Marine Resources in Indonesia.